Theoretical Concepts of Crime and Practices in Urban Planning and Design Process for Safe Urban Life - Haider, Mohammad Ali; Iamtrakul, Pawinee (International Journal of Building, Urban, Interior and Landscape Technology, 2018)
Crime is a serious concern from the very beginning of human civilization and several theoretical concepts are addressing the ‘social crime’ issue minimization crime without compromising harmonized economic activities and environmental safety. However, urbanization is very closely associated with social crime, for example, rapid urbanization which includes architectural planning accommodating housing and transportation, level of accessibility and other outdoor spaces can influence crime and fear of delinquency to the city dwellers. This review explored the relationship between crime and urbanization from the existing theoretical concepts of crime in urban planning, design and development viewpoints. We also discussed the applications of theoretical concepts in urban planning processes to minimize the crime and its possible prevention strategies. More precisely, place-based theoretical concepts of crime depict the urban socio-physical environment with socially disorganized locations of the city and the causes of social disorder and pave a way for the local government to take and implement strategic plans for ensuring good governance of the city. These concepts also demonstrate crime pattern, hotspots formation, causes-effects and how to prevent crime hotspots. Thus, taking these concepts into consideration, a significant portion of crime can be reduced in modern planned urbanization. Besides, continuous refinement of 1st, 2nd, and 3rd generation concepts of crime prevention through environmental design (CPTED) is worth considering in urban planning and design process preventing crime and safe urban environment initiative. Finally, further studies are needed to comprehend crime avoidance actions in urban planning and design process for safe urban life, particularly in developing countries.